Posible influencia de los rametes en la estructura poblacional y distribución del árbol gigante Warszewiczia uxpanapensis, Cordillera de Tilarán, Costa Rica - Brenes Cambronero, Liz (2006)
The distribution and population structure of Warszewiczia (=Elaeagia) uxpanapensis , a tree that reaches a height of 45 m, a DBH of 1.40 m and 8 m tall buttresses, was studied on two 1-ha plots of premontane pluvial forest. It had a frequency of 49 % and a mean dominance of 6.5 %. The adult distribution was random (mean distance to the nearest neighboring tree in plot 1, it was 14.26 m, n= 15; Clark-Evans Index (IC-E)= 1.07; in plot 2, it was 15.33 m, n= 18, IC-E= 1.34,). The seedlings represented 60.3 % of the sampled population (plot 1, n= 94; plot 2, n= 85). This species has a very high capability of propagating itself vegetatively through clones (“ramets”), which influence its distribution and population structure. With a ramet density in plot 1 of 0.8 and in plot 2 of 0.3/ 100 m2, its propagation could be from fallen trees or branches (which also create clearings in the forest) or from standing trees and even live branches that produce adventitious roots.